2013
DOI: 10.1159/000352048
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Brain Lesions in Relation to Hyperperfusion from Subacute to Chronic Stages after Experimental Subarachnoid Hemorrhage: A Multiparametric MRI Study

Abstract: Background: The pathogenesis of delayed cerebral injury after aneurysmal subarachnoid hemorrhage (SAH) is largely unresolved. In particular, the progression and interplay of tissue and perfusion changes, which can significantly affect the outcome, remain unclear. Only a few studies have assessed pathophysiological developments between subacute and chronic time points after SAH, which may be ideally studied with noninvasive methods in standardized animal models. Therefore, our objective was to characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…MR imaging has well-documented advantages and reliability compared with CT in detecting cerebral edema, acute hydrocephalus (6-8), white matter injury (9-11) and ischemic lesions (12, 13). Imaging in the acute phase of SAH presentation may lead to better delineation of the early brain injury caused by SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR imaging has well-documented advantages and reliability compared with CT in detecting cerebral edema, acute hydrocephalus (6-8), white matter injury (9-11) and ischemic lesions (12, 13). Imaging in the acute phase of SAH presentation may lead to better delineation of the early brain injury caused by SAH.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a non-invasive method for collecting structural, physiological and functional imaging data with high spatial resolution (5). It has been widely used for detecting brain injuries such as cerebral edema, acute hydrocephalus (6-8), white matter injury (9-11) and ischemic lesions (12, 13) caused by various central nervous system diseases. However, due to longer acquisition time and difficulty in performing of MRI compared to CT scans and the high risk of re-bleeding in SAH patients, MRI is rarely performed clinically for the patients in the acute setting after SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in microvascular permeability after SAH is also interrelated with delayed cerebral ischemia and poor prognosis (Germano et al 2000). Tiebosch et al have reported that vasogenic edema formation and blood-brain barrier permeability on day 7 after SAH were positively correlated with hyperperfusion on day 2 after SAH (Tiebosch et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A sample size of 16 to 17 animals per group was a priori calculated based on the Chi-square test with a hypothesized valproate-induced lesion reduction from 300 (±75) mm 3 to 200 (±75) mm 3 and 35% mortality before day 3, based on previous research from our group. 17 Rats were randomized in a 2×2 design with randomization through an electronically generated list by an independent person with allocation concealment. Animals were treated daily, starting 4 weeks before SAH induction, with 0.2 mL/100 g of 100 mg/mL intraperitoneally administered sodium valproate (200 mg/kg; valproate groups) or saline (with a similar osmolarity and pH as valproate; vehicle groups).…”
Section: Methodsmentioning
confidence: 99%